2018
DOI: 10.3920/bm2017.0107
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentum L930BB and Bifidobacterium animalis subsp. animalis IM386 initiate signalling pathways involved in intestinal epithelial barrier protection

Abstract: The manipulation of intestinal microbiota with beneficial microbes represents a promising alternative or adjunct therapy in gastrointestinal disorders and inflammation. The current study aims to clarify the signalling pathways and evaluate the possible beneficial effects of the combination of two strains. We used a dextran sulphate sodium (DSS)-induced mouse model of colitis. RNA extracted from the middle part of the colon tissue was used for examination of the global gene expression with Affymetrix microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Alterations in these pathways have been reported in different MtS models, including increases, decreases and no modifications in their activities [53,[57][58][59]. Even though only few inconsistent results were reported regarding the effect of probiotics and synbiotics on those pathways [60][61][62][63][64][65][66], their role in the phosphorylation and subsequent activation of nNOS is well demonstrated [27,51,67,68]. We found that the inhibition of either PKC or PI3K with calfostin C or LY294002 respectively reduced EFS-induced NO release in a similar extent in the three experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in these pathways have been reported in different MtS models, including increases, decreases and no modifications in their activities [53,[57][58][59]. Even though only few inconsistent results were reported regarding the effect of probiotics and synbiotics on those pathways [60][61][62][63][64][65][66], their role in the phosphorylation and subsequent activation of nNOS is well demonstrated [27,51,67,68]. We found that the inhibition of either PKC or PI3K with calfostin C or LY294002 respectively reduced EFS-induced NO release in a similar extent in the three experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…At the level of the Actinobacteria phylum, GOS-Lu cohort shows an increase in this bacteria, mainly due to more abundant populations of Bifidobacteriaceae family, and specially of Bifidobacterium genus, being associated to health benefits including protection against pro-inflammatory gut conditions but also against CRC ( Table 1 and Figure 9 ). This protection against CRC has been associated to NF-kB repression by these probiotic bacteria ( Roller et al, 2004a ; Kim et al, 2010 ; Celiberto et al, 2017 ; Paveljšek et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also difficult to compare the results of different studies where different protocols as well as different cell lines are used. Furthermore, cell lines only represent an approximation of the real biological state, so it is essential that these studies are supported by more complex models such as organoids or experiments on animal models, which were also the starting point of our study (Paveljšek et al, 2018).…”
Section: Probiotic Impact On the Intestinal Epithelial Barriermentioning
confidence: 99%
“…Despite intensive research, the mechanisms behind cell signalling are not yet well understood. Our previous study on DSS‐induced colitic mouse model shows that a combination of two probiotic strains helped in the regeneration of the intestinal epithelium during pathogenesis via pathways that are known downstream targets of TLR2 (Paveljšek et al, 2018). In the present study, we aimed to reveal the TLR2‐mediated signalling pathways that are probably responsible for the regulation of the intestinal epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%